2020
DOI: 10.5530/pj.2020.12.170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Afghan Senjed (Elaeagnus Angustifolia L.) Leaves Aqueous alcoholic Extract on Blood Glucose Level of Diabetic Rats

Abstract: Introduction: Diabetes mellitus is a metabolic disorder, which affects many people throughout the world. The inefficacy and multiple side effects of most synthetic anti-diabetic drugs are reported by various studies. Thus, many researchers are focused on the use of medicinal plants as safe and potent anti-hyperglycemic drugs. The aim of this study is the evaluation of the effect of Afghan senjed (Elaeagnus Angustifolia L.) leaves aqueous alcoholic extract on blood glucose level of diabetic rats. Methods: Rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Researchers all over the world are also focused on the effect of medicinal plants and their constituents on diabetes, because of their fewer side effects than synthetic drugs. [12][13][14] In traditional medicine, it is recommended to use herbs combinations, because there are some reports that multiple herbs combinations have more effects than individual herbs. [15] Many researchers consider the combination therapy as a new and effective therapeutic strategy for controlling hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers all over the world are also focused on the effect of medicinal plants and their constituents on diabetes, because of their fewer side effects than synthetic drugs. [12][13][14] In traditional medicine, it is recommended to use herbs combinations, because there are some reports that multiple herbs combinations have more effects than individual herbs. [15] Many researchers consider the combination therapy as a new and effective therapeutic strategy for controlling hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies showed that there is a glucose intolerance in almost all diabetic patients (30). Also, the glucose tolerance test indicates insulin secretion and its function, so GTT is used to evaluate insulin secretion and sensitivity (6). The results of this study showed that A. Repens extract could decrease the blood glucose level after administration of a glucose load.…”
Section: Discussionmentioning
confidence: 66%
“…Most of these complications have resulted from chronic hyperglycemia (4). Therefore, the main purpose of diabetes treatment is the prevention of its complications through the control of hyperglycemia (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…7 Many researchers are focused on the use of natural compounds and medicinal plants. 28 There are many plants and nuts such as Convulvulus pluricaulis, Evolvulus alsinoides, Canscora decussate, Juglans regia which are used for enhancement of learning and memory. 18,[29][30][31] In general, nuts have various beneficial constituents.…”
Section: Discussionmentioning
confidence: 99%